2004
DOI: 10.1056/nejmoa033280
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone, Valacyclovir, or the Combination for Vestibular Neuritis

Abstract: Methylprednisolone significantly improves the recovery of peripheral vestibular function in patients with vestibular neuritis, whereas valacyclovir does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
214
0
28

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(256 citation statements)
references
References 26 publications
8
214
0
28
Order By: Relevance
“…This study confirms prior reports showing peripheral vestibular function improvement in patients with AUV receiving glucocorticoids on admission [3,20,21]. Additionally, we have shown that the improvement in canal paresis with glucocorticoid treatment correlates with a reduction in the degree of nystagmus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirms prior reports showing peripheral vestibular function improvement in patients with AUV receiving glucocorticoids on admission [3,20,21]. Additionally, we have shown that the improvement in canal paresis with glucocorticoid treatment correlates with a reduction in the degree of nystagmus.…”
Section: Discussionsupporting
confidence: 92%
“…One study probed the effects of corticosteroids with and without antivirals and concluded that methylprednisolone, but not valacyclovir, improves the recovery of vestibular function in these patients [21]. Other studies have confirmed the effects of glucocorticoids on peripheral vestibular function following acute AUV [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Such an analysis is particularly important in the light of recent suggestions that steroid treatment for acute VN improves peripheral-vestibular recovery (albeit measured with the caloric test and without symptom assessment) [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…89 However, the efficacy of corticosteroids is controversial. A recent Cochrane review concluded that there is currently insufficient evidence to support the use of corticosteroids in patients with idiopathic acute vestibular dysfunction.…”
mentioning
confidence: 99%